A new genus and species of Eucoilinae (Hymenoptera, Cynipoidea, Figitidae) parasitoid of Euxesta eluta Loew (Diptera, Otitidae) attacked Bt sweet corn in Argentina - Gallardo, Fabiana Edith (2017)
Euxestophaga Gallardo, a new genus of Eucoilinae (Hymenoptera, Cynipoidea, Figitidae) and Euxestophaga argentinensis Gallardo, sp. n. from Argentina, are described and illustrated. This new genus belongs to the Ganaspini and morphologically resembles Epicoela Borgmeier and Striatovertex Schick, Forshage and Nordlander. A key to differentiate these genera is given. Specimens were reared from pupae of Euxesta eluta Loew (Diptera: Otitidae), attacked Bt sweet corn in Santa Fe province and other in Tucumán province (Argentina).